Effect of Qingre Jiedu Huoxue Huayu Recipe on blood stasis and toxin syndrome in patients with non-ST segment elevation acute coronary syndrome, serum Lp-PLA2, TNF- α, and PIGF expression level - Zifu, Tan; Jiaquan, Li; Juan, Zhang (Cellular and Molecular Biology, 2022)
The pathological basis of non-ST-segment elevation acute coronary syndrome (NSTE-ACS) is severe coronary stenosis, unstable plaque erosion, and rupture, resulting in coronary blood flow reduction and myocardial ischemia, leading to acute thrombosis cardiovascular disease events. This subject intends to study the treatment of NSTE-ACS patients with blood stasis and toxin syndrome by Qingre Jiedu Huoxue Huayu Decoction, observe its clinical efficacy, and explore the effects of serum lipoprotein phospholipase A2 (Lp-PLA2) and tumor necrosis factor- α (TNF- α), the effect of placental growth factor (PIGF) expression. In this study, 100 patients with blood stasis and toxin syndrome of NSTE-ACS treated in the cardiovascular department of Enshi National Hospital from August 2020 to August 2021 were selected as the research object. They were randomly divided into traditional Chinese medicine comprehensive treatment groups and conventional western medicine control groups, with 50 cases. The conventional western medicine control group was treated with hydroclopidogrel tablets orally, and the comprehensive treatment group of traditional Chinese medicine combined with Qingre Jiedu Huoxue Huayu formula orally. The patients in both groups were treated for four weeks. The results showed that after treatment, the practical clinical rate of the comprehensive treatment group was significantly higher than that of the conventional western medicine control group. After treatment, the TCM syndrome score, angina pectoris attack duration, and angina pectoris attack frequency, myocardial zymogram index level, serum Lp-PLA2 and TNF of the two groups were measured- α. The levels of PIGF were significantly lower than those before treatment. The decline of the above indexes in the comprehensive treatment group of traditional Chinese medicine was significantly better than that in the control group of conventional Western Medicine (P<0.05). The incidence of MACE events in the TCM Comprehensive treatment group was significantly lower than that in the conventional western medicine control group (P <0.05).